The Importance of Knowledge Base among Kindergartner Teachers on Language Structure in Teaching Reading Effectively - Kilat, Christie Mae (JPAIR Multidisciplinary Research, 2019)
Reading plays a vital role in learning, and yet it is a common problem in many classrooms nowadays. Many researchers are looking for a solution to this problem. Various methods and strategies are needed to come to a solution. By then, the role of the teacher comes in; he will implement these methods and strategies intended for reading. As the teaching-learning process, still problem arises if the teacher has not had enough knowledge on how to effectively teach reading.  This study was conducted to determine the knowledge base of kindergartner teachers of Language Structure in teaching reading effectively in the schools of Gitagum, Libertad and Initao, Misamis Oriental. This descriptive type of study involves thirty-three kindergartner teachers in the three municipalities of Misamis Oriental based on the District offices enrolment. The respondents were given a survey questionnaire to rate themselves on their level of knowledge on the basic components of reading and to test themselves on their knowledge and abilities on Language Structures. The data were analyzed using descriptive statistics like mean, percentage, and t-test.  The results showed inconsistency in their level of knowledge, the outcome of the knowledge, and ability test. Hence, the kindergartner teachers still lack knowledge of language structure and require in-depth training and seminar-workshop.
Keywords: Teacher Knowledge; Kindergartner Teacher; Language Structure; Descriptive design; Gitagum; Libertad; Initao; Misamis Oriental; Philippines